2018
DOI: 10.21037/atm.2018.07.32
|View full text |Cite
|
Sign up to set email alerts
|

Insulin autoimmune syndrome: from diagnosis to clinical management

Abstract: Autoimmune forms of hypoglycemia are a rare cause of low blood sugar levels among Caucasians, and often go misdiagnosed, exposing patients to lengthy series of pointless, potentially harmful and expensive tests. There are two types of autoimmune hypoglycemia. One is insulin autoimmune syndrome (IAS), which is characterized by hyperinsulinemic hypoglycemia, elevated insulin autoantibody (IAA) titers, no prior exposure to exogenous insulin, and no of pathological abnormalities of the pancreatic islets. This cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
137
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(153 citation statements)
references
References 120 publications
(186 reference statements)
7
137
0
9
Order By: Relevance
“…The rate at which hypoglycemia triggered the diagnosis was high, and the rate of hypoglycemia was also high overall. It was indicated that hypoglycemia can be seen even in the previous report [1,2,19]. In the present survey, hypoglycemia was observed in 85.7% of Japanese cases and was considered a major symptom.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…The rate at which hypoglycemia triggered the diagnosis was high, and the rate of hypoglycemia was also high overall. It was indicated that hypoglycemia can be seen even in the previous report [1,2,19]. In the present survey, hypoglycemia was observed in 85.7% of Japanese cases and was considered a major symptom.…”
Section: Discussionmentioning
confidence: 45%
“…IGF-1. IGF-1 may be effective against the increased blood glucose caused by TBIR [2,6,12,19]. Considering that IGF-1 causes insulin-like action via the IGF-1 receptor in skeletal muscle, a reduction in blood glucose was expected in patients suffering from TBIR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin autoimmune hypoglycaemia (IAH) is characterized by autoantibodies against endogenous insulin without any prior exposure to exogenous insulin. Also known as Hirata disease, IAH is most commonly reported from Japan …”
Section: Introductionmentioning
confidence: 99%
“…Insulin auto‐antibodies (IAA) are associated with other autoimmune diseases, medications (sulfhydryl group containing), haematological disorders (Multiple Myeloma/Monoclonal Gammopathy of Undetermined Significance (MGUS), Non‐Hodgkin's B‐cell lymphoma) and infections (Hepatitis C virus) . As reported from Japan, about 80% of the cases of IAH go into spontaneous remission; but due to lack of awareness about the condition in areas outside Japan, the diagnosis and management remain challenging …”
Section: Introductionmentioning
confidence: 99%